(untitled) (Хабаршы. Психология және социология сериясы, 2022)
The role of information technology has become very important in the era of globalization and mod-ernization, especially in various fields, such as the field of education. The online learning process is one whose performance is greatly influenced by the ability of teachers to use technology to provide learning materials. The presence of e-learning in Indonesia can have an influence on student learning motivation. One of them is the impact on his learning attitude. The purpose of this study was to determine the influ-ence of self-regulated learning, self-efficacy on student learning motivation at SMPN X. Samples totaling 220 students were taken using non-probability sampling techniques in the form of simple random sam-pling. The data collection method uses a learning motivation scale of α value = 0.735, a self-regulated learning scale of α value = 0.744 and a self-efficacy scale of α value = 0.739. The analysis used is multiple linear regression analysis. The results of this study show that there is a positive influence with t count > t table of 1,945 on self-regulated learning on learning motivation which means that the higher the self-regulated learning , the higher the motivation to learn, self-efficacy has a positive effect with sig.( p)= 0.021 (sig. <0.050) on learning motivation which means that the higher the self-efficacy , the higher the motivation to learn, then self-regulated learning and self-efficacy simultaneously have a positive effect with sig.( p)= 0.001 (sig. <0.050) to learning motivation which means that the higher the self-regulated learning and self-efficacy , the higher the motivation to learn in students. The coefficient of determination known to Rsquare is 0.044 which means that the variables self-regulated learning and self-efficacy together affect learning motivation by 4.4% and are influenced by other variables by 95.6%. Key words: learning motivation, self regulated learning, self efficacy.